METODE MENGAJAR DAN MOTIVASI TERHADAP HASIL BELAJAR KETERAMPILAN SERVIS FLATTENIS LAPANGAN(STUDI EKSPERIMEN PADA MAHASISWA FIK UNM MAKASSAR) - AS, Hasbunallah; Bismar, Ahmad Rum (UNIVERSITAS NEGERI MAKASSAR, 2020)
The aim of this experimental study was todetermine the effect of all teaching methods, part, mixed and motivation result learning toward of flat service skill courts tennis. Learning motivation is divided into two parts, namely high andlow.This research was conducted at Faculty of Sport ScienceState University of Macassar,the academic year 2014/2015. Experimental using factorial design method 2x3. The sample consisted of 60 students were divided into 6 groups, each consisting of 10 students. Data analysis technique is a two-way analysis of variance (ANOVA) followed by Tukey's test at a significance level of Î±= 0.05. The results of this study indicate that ( (1) overall teaching methods higher effect of the part teacing methods on learning outcomes flat tennis service skills (2) overall teaching methods lower effect of the part teacing methods on learning outcomes flat tennis service skills, (3) overall teaching methods lower effect of the part teacing methods on learning outcomes flat tennis service skills,(4) there is interaction between the overall teaching methods, part teaching methods and combined teaching methods and learning motivation outcomes flat tennis service skills,(5) overall teaching methods higher effect of the part teacing methods on learning outcomes flat tennis service skillsusing a high learning motivation, (6) overall teaching methods lower effect of the part teacing methods on learning outcomes flat tennis service skillsusing a high learning motivation, (7) part teaching methods lower effect of the combined teacing methods on learning outcomes flat tennis service skillsusing a high learning motivation, (8) overall teaching methods higher effect of the part teacing methods on learning outcomes flat tennis service skillsusing a low learning motivation, (9) overall teaching methods lower effect of the part teacing methods on learning outcomes flat tennis service skillsusing a low learning motivation, (10) part teaching methods lower effect of the combined teacing methods on learning outcomes flat tennis service skillsusing a low learning motivation.